Family Behavioral Repertoires and Family Interaction Influence the Adaptive Behaviors of Individuals With Hikikomori - Nonaka, Shunsuke; Shimada, Hironori; Sakai, Motohiro (Frontiers in Psychiatry, 2020)
Background: Family support is key in the initial stages of psychological support for individuals with hikikomori. However, it remains necessary to confirm the relationship between families’ cognitive behavioral factors and the severity of hikikomori to understand ways of improving hikikomori. We examined the influences of family behavioral repertoires for coping with hikikomori and family interaction on the adaptive behaviors of individuals with hikikomori. We employed a control group to examine whether the influence of the adaptive behaviors is unique to families of individuals with hikikomori. Methods: We asked 185 parents of individuals with hikikomori (hikikomori group) and 460 parents of individuals with no experience of hikikomori (control group) to complete the Family Behavioral Repertoire Scale for coping with hikikomori (FBS-H), the Family Interaction Scale for Hikikomori (FIS-H), and the Adaptive Behaviors Scale for Hikikomori (ABS-H). Using the subscales of the ABS-H as the dependent variables, we conducted hierarchical multiple regression analyses wherein family behavioral repertoire was added in Step 1, experience frequency and cognition of contingency as control values were added in Step 2, family interaction was added in Step 3, and the interaction terms were added in Step 4. Results: The ABS-H total score and subscale scores were significantly lower in the hikikomori group than in the control group. The social participation subscale showed the largest difference, while the family subscale showed the smallest. In the hikikomori group, we observed a significant adjusted R2 for the family and value subscales (Step 1). The ΔR2 in Step 3 was significant for the interaction and family subscales. In the control group, significant adjusted R2 values were found for all ABS-H subscales in Step 1, but the ΔR2 in Step 3 was not significant for any subscales. Conclusion: Family-related cognitive behavioral factors such as family behavioral repertoire and family interaction appear to relate to improvement in hikikomori. Of course, the findings warrant further investigation because we did not examine the longitudinal, causal relations between these variables. In the future, we might also test the effect of family support interventions that target families’ behavioral repertoire and family interaction.